UJI FITOKIMIA EKSTRAK METANOL KULIT BATANG KETEPENG CINA (Cassia alata L.) SEBAGAI KANDIDAT OBAT TRADISIONAL - Mirza, Ira; Aini, Qurratu; Rizki, Cut Novrita (FKIP Universitas Tanjungpura, 2025)
This study aims to identify the content of phytochemical compounds in the methanol extract of the bark of Ketepeng Cina (Cassia alata L.) as an initial step in the development of traditional medicine. The Cassia alata plant is known to have various potential pharmacological properties. This study used a qualitative descriptive research design to determine the results of the phytochemical test. This test was conducted at the Research Laboratory of the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Syiah Kuala University. Extraction was carried out using methanol solvents through the maceration method, then continued with phytochemical tests to detect the presence of secondary metabolite compounds such as alkaloids, flavonoids, saponins, tannins, steroids, and triterpenoids. The test results showed that the methanol extract of the bark of Cassia alata contains several active compounds including steroids, flavonoids, phenolics and tannins which have the potential as raw materials for traditional medicine. These findings support the use of this plant in the development of phytopharmaceuticals and encourage further research for pharmacology and toxicity tests. Keywords: Cassia alata L., Phytochemicals, Methanol extract, Traditional medicine